Effect of the regional environment on the skin properties and the early wrinkles in young Chinese women. Issue 4 (25th March 2014) - Kim, E. J.; Han, J. Y.; Lee, H. K.; He, Q. Q.; Cho, J. C.; Wei, L.; Wang, X.; Li, L.; Wei, L.; Liang, H.; Gao, X.; Kim, B. J.; et al.
Abstract : Background: There are ethnic differences in the skin characteristics, also the skin is susceptible to be influenced by the external environment such as UV radiation and the climates. It can be shown that the skin in same race or twins varies by the environment. Objectives: This study was designed to investigate the skin characteristics and the early wrinkles of young Chinese women from four different regions, and to identify the correlation among the wrinkles, the other skin characteristics, and environmental conditions. Methods: A total of 441 healthy Chinese women aged between 20 and 35 years participated in the study: 110 from Beijing, 110 from Shanghai, 111 from Wuhan, and 110 from Guangzhou. The skin hydration, sebum contents, TEWL, pH, elasticity, and wrinkles were measured on the crow's feet area. Results: There were regional differences in the skin characteristics and the wrinkles. Beijing women had dry skin and more wrinkles, but Guangzhou women had high sebum contents, low pH, and less wrinkles ( P  < 0.01). Shanghai women's TEWL and Wuhan's women's skin elasticity were higher compared with that of women from other regions. The wrinkles' form (area, depth, and length) was different from region to region. Beijing women's wrinkles were deep and large, but Guangzhou women's wrinkles were shallow and small. The skin physical parameters that influenced the wrinkles were low sebum content and hydration, high TEWL, and pH ( P  < 0.05). Conclusion: In the Chinese women aged 20–35 years, the skin was influenced by the climates, so they had regionally a different skin. The skin hydration, sebum contents, TEWL, and pH can affect the early wrinkle formation than skin elasticity.